DAMPAK SPIRITUAL LEADERSHIP DAN QWL TERHADAP OCB DENGAN KEPUASANKERJA SEBAGAI VARIABEL INTERVENING PEGAWAI BADAN PERENCANAAN PEMBANGUNAN, PENELITIAN DAN PENGEMBANGAN DAERAH KOTA PASURUAN - Dimas Candrananta; ARIEF PURWANTO (BADAN PENERBITAN UNIVERSITAS WIDYAGAMA, 2022)
ABSTRACT The purpose of the study is to obtain empirical evidence of spiritual leadership and QWL ability in improving OCB, both directly and through intervening job satisfaction. This type of research is quantitative research, and the method used is SEM-PLS. The data was obtained through a questionnaire distributed to 38 employees of Bappelitbangda Pasuruan City, which was taken by census. The research findings show that QWL is able to increase OCB, both directly and through intervening job satisfaction. However, spiritual leadership is not able to improve OCB, either directly or through intervening job satisfaction. This empirical evidence is supported by descriptive statistics that are at high average values. This research has made various efforts to reduce or eliminate the occurrence of